Modeling of Roll-Heave-Pitch Motions of a Ram Wing Translating over Non-uniform Surface - Matveev, Konstantin I. (Journal of marine science and application, 2019)
Ground-effect vehicles flying close to water or ground often employ ram wings which generate aerodynamic lift primarily on their lower surfaces. The subject of this paper is the 3-DOF modeling of roll, heave, and pitch motions of such a wing in the presence of surface waves and other ground non-uniformities. The potential-flow extreme-ground-effect theory is applied for calculating unsteady pressure distribution under the wing which defines instantaneous lift force and moments. Dynamic simulations of a selected ram wing configuration are carried out in the presence of surface waves of various headings and wavelengths, as well as for transient flights over a ground obstacle. The largest amplitudes of the vehicle motions are observed in beam waves when the periods of the encounter are long. Nonlinear effects are more pronounced for pitch angles than for roll and heave. The present method can be adapted for modeling of air-supported lifting surfaces on fast marine vehicles.